Acceleration Pattern and Neuromuscular Response of the Spine and Ankle During the Limits-of-Stability Test - Kuo, Fang-Chuan (Journal of strength and conditioning research, 2020)
Kuo, FC. Acceleration pattern and neuromuscular response of the spine and ankle during the limits-of-stability test. J Strength Cond Res 34(3): 857-865, 2020-This study aimed to explore the acceleration amplitude, frequency, and electromyography (EMG) activity at the spine, pelvis, and lower extremities under various platform-stability settings. Thirty two young adults (16 men and 16 women) were recruited from a university in Taiwan. A balance system for limits-of-stability testing was used with 2 platform stability settings (i.e., level 4 and static). An inertial motion system and a telemetry EMG system were used to record kinematic and EMG data. Consequently, compared with the level 4 setting, the static-level setting required greater thoracic lateral flexion, pelvic course, and pelvic pitch; greater acceleration amplitudes of the spine, pelvis, and thigh; and greater acceleration frequencies at the shin and ankle. Participants exhibited a significant increase in knee flexion, ankle abduction, foot acceleration, and activity of the rectus femoris and tibialis anterior muscles when the platform stability was decreased. In addition, higher median frequencies of the spine and pelvis and larger amplitudes of the foot were observed under the level 4 setting. The men exhibited a larger range of motion in lumbar joint and thoracic rotation than did the women. To maintain stability, subjects must readjust their head, spine, and ankle movement amplitudes and frequencies depending on the platform stability. The study findings suggest the use of static platform settings for spine control facilitation and unstable platform settings for proprioception and muscle strengthening of lower extremity.